Student Engagement as a Mediator of Academic Self-Efficacy and Academic Performance in Islamic Boarding School Students - Putra, Rahman Pranovri; Ramadhanti, Auliya; Setiawati, Farida Agus; Jannah, Ega Nurratul; Puhka, Prakash (Journal for Lesson and Learning Studies, 2024)
Academic performance problems that are still rampant in various boarding schools are often triggered by students' lack of active participation and confidence in their academic abilities. This study aims to analyze the effect of academic self-efficacy on academic performance with student engagement as a mediator for students in Islamic boarding schools. The method in this study is quantitative research with an ex-post facto approach. The sample in this study was determined using multistage random sampling technique with a total of 308 student. The instruments used in this study were academic self-efficacy scale with dimensions of level, generality, and strength, student engagement scale with dimensions of emotional engagement, cognitive engagement, and behavioural engagement, and academic performance measured by referring to report card data. The data obtained were analysed quantitatively using the PROCESS v4.2 macro of the Hayes 4 model through the SPSS Version 25 application. The results of this study indicate that academic self-efficacy, student engagement, and academic performance of students in boarding schools are positively related, and student engagement acts as a mediator between academic self-efficacy and academic performance. Students with high self-efficacy are more confident in learning can solve problems more effectively and are more engaged in learning, thus improving academic achievement.